IMPACT OF MOTIVATION ON EMPLOYEE PERFORMANCE IN PRINTING INDUSTRY– A STUDY IN RURAL AREAS OF KANNIYAKUMARI DISTRICT (International Journal of Food and Nutritional Sciences, 2022)
The Printing industry played a vital role in the freedom struggle and other revolutionary struggles for social justice and against fascist dictators. In India the British government started the printing industry. In the present liberalized and globalized Indian economy, the country has noticed a rapid growth of industry in the fields of marketing, journalism and education fields. Introduction of technology and computers gave accelerating momentum for the industry and invited many dynamic and innovative entrepreneurs through small and medium enterprises. This printing industry paved the way for the growth of secondary industry like packaging and Transport industry. In fact, it gives jobs for educated as well as uneducated youth in the country. The government of India and some state governments offer printing technology courses for innovation and growth of the industry in the form of education diploma or undergraduate degree or post graduate degrees. This paper intends to understand the impact of motivation on printing employees. The study has been made by conducting a survey in rural areas of Kanniyakumari District of Tamil Nadu State. For that, the researcher collected90samples from the respondents and percentage, Garret ranking method and Chi- squre test used for this study